Optimalisasi Sukuk Wakaf Dalam Pembangunan Ekonomi Syariah - Andini, Bunga; Winario, Mohd (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
This research aims to analyze the optimization of waqf sukuk in sharia economic development, with a focus on the potential and challenges faced in its implementation in Indonesia. The method used in this research is a qualitative approach, which involves literature study, interviews with experts in the field of waqf and sharia finance, as well as analysis of policy documents related to the development of waqf sukuk. The data collected was then analyzed descriptively to provide a comprehensive picture of the implementation of waqf sukuk in Indonesia. The research results show that waqf sukuk have great potential in funding social projects that support the welfare of the people, such as the development of education, health and infrastructure. However, there are several challenges in developing waqf sukuk, including a lack of understanding among the community and waqf managers, as well as regulatory obstacles that limit its growth. This research also found that support for more progressive government policies and increased cooperation between sharia financial institutions, waqf managers and the government are very important to increase the optimization of waqf sukuk as a sustainable sharia economic financing instrument.